Peran Deep Learning dalam Proses Pembelajaran Pendidikan Agama Islam terhadap Pengembangan Kompetensi Berpikir Kritis Siswa - Nayla Nur Rahmawati; Taqiyyah Jannatul Ma’wa; Riva Syifaullana; Muhammad Ismail Habibullah; Iqbal Aliffiansyah; Izzatul Mardhiah (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This research examines the implementation of the Deep Learning approach in Islamic Religious Education (PAI) learning at SMAN 61 Jakarta and its contribution to the development of students' critical thinking skills. This study was conducted due to the need for a learning model that encourages students to understand religious concepts through active, reflective, and meaningful learning experiences. The purpose of this research is to describe the implementation of Deep Learning in PAI learning and its influence on the development of students' critical thinking skills. This study employs a qualitative method with a descriptive research design, using interviews, classroom observations, and documentation as data collection techniques. The findings indicate that the Deep Learning approach supports students in participating more actively in discussions, analyzing religious issues related to real-life situations, and constructing arguments based on their own understanding. Students also demonstrate improvement in evaluating information, considering diverse perspectives, and providing more reflective responses to classroom problems. The study further identifies several challenges, including limited digital facilities, varying levels of student participation, and teachers’ readiness in managing diverse learning strategies and media. These findings suggest that Deep Learning has strong potential to enhance students’ critical thinking skills when applied systematically and designed to foster active participation and meaningful exploration during the learning process.